PENGARUH MENTAL HEALTH, REWARD DAN PUNISHMENT TERHADAP PRODUKTIVITAS KERJA KARYAWAN DENGAN SEMANGAT KERJA KARYAWAN SEBAGAI VARIABEL INTERVENING PADA PT. TELUK LUAS PADANG - Muhamad Faris; Nanda Harry Mardika (Yayasan Tri Edukasi Ilmiah, 2024)
This Research Aims To Find Out How Big The Effect Of Mental Health, Reward And Punishment Discussion On Employee Work Productivity With Employee Morale As An Intervening Variable At Pt. Padang Broad Bay. The analytical method used is multiple regression analysis. The results obtained based on the partial test (T test) are obtained: There is no significant effect of mental health on morale at PT. Teluk Lebar Padang, there is a significant influence of reward on work enthusiasm at PT. Teluk Lebar Padang, there is a significant effect of punishment on morale at PT. Teluk Lebar Padang, There is no significant effect of Mental Health on Work Productivity at PT. Teluk Lebar Padang, there is no significant effect of reward on work productivity at PT. Teluk Lebar Padang, there is a significant effect of punishment on work productivity at PT. Teluk Lebar Padang, there is a significant effect of morale on work productivity at PT. Teluk Lebar Padang, Work Enthusiasm cannot mediate the effect between Mental Health on Work Productivity, Work Morale can mediate the effect between Rewards on Work Productivity, Work Morale can mediate the effect between Punishment on Work Productivity